2016
DOI: 10.1111/jne.12352
|View full text |Cite
|
Sign up to set email alerts
|

Combining Cadherin Expression with Molecular Markers Discriminates Invasiveness in Growth Hormone and Prolactin Pituitary Adenomas

Abstract: Although growth hormone (GH)- and prolactin (PRL)-secreting pituitary adenomas are considered benign, in many patients, tumour growth and/or invasion constitute a particular challenge. In other tumours, progression relies in part on dysfunction of intercellular adhesion mediated by the large family of cadherins. In the present study, we have explored the contribution of cadherins in GH and PRL adenoma pathogenesis, and evaluated whether this class of adherence molecules was related to tumour invasiveness. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 49 publications
2
34
1
Order By: Relevance
“…Our results are in agreement with previous studies indicating that lower membranous E-cadherin levels are associated with aggressive features in pituitary tumours. 14,17,20 Importantly, our results revealed that loss of membranous E-cadherin localization is associated with poor response to SSAs in acromegaly patients, in line with a previous study. 14 Intriguingly, we observed a negative association between E-cadherin and SSTR5 expression in GH-producing tumours.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in agreement with previous studies indicating that lower membranous E-cadherin levels are associated with aggressive features in pituitary tumours. 14,17,20 Importantly, our results revealed that loss of membranous E-cadherin localization is associated with poor response to SSAs in acromegaly patients, in line with a previous study. 14 Intriguingly, we observed a negative association between E-cadherin and SSTR5 expression in GH-producing tumours.…”
Section: Discussionsupporting
confidence: 92%
“…14,[17][18][19][20] However, the association between the loss of E-cadherin expression and aggressiveness of GH-producing tumours has yielded conflicting results. 14,[17][18][19][20] E-cadherin expression levels are also correlated with GH-producing tumour histological subtypes. Thus, whereas high E-cadherin expression levels are found in densely granulated somatotroph adenomas (DGSAs) tumours, low or absent E-cadherin expression is observed in sparsely granulated somatotroph adenomas (SGSAs).…”
Section: Consensus Guidelines Recommend Somatostatin Analogues (Ssas)mentioning
confidence: 99%
See 1 more Smart Citation
“…The results are quite controversial regarding the role of these markers in the invasiveness of pituitary adenomas. Some studies indicate an association of markers with tumor invasiveness ( 6 , 7 , 9 ), while others do not recognize this association ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Deregulated expression and activity of some cadherin proteins are frequently observed in human PAs and are inferred to contribute to the pathogenesis of PAs. [18][19][20] In addition, CDH23 forms heterodimers and functions closely with protocadherin-related 15 (PCDH15), whose encoding gene is located near a genetic susceptibility locus for pituitary adenoma according to our previous work. 7 These findings further suggest mutations in CDH23 as a potential genetic risk factor for this familial PA.…”
mentioning
confidence: 99%